Morphological features of breast cancer circulating tumor cells in blood after physical and biological type of isolation - Jesenko, Tanja (Radiology and oncology (Ljubljana), 2021)
Background. Circulating tumor cells (CTCs) have become an important biomarker in breast cancer. Different iso-lation tech-niques based on their biological or physical features were established. Currently, the most widely used methods for visualization after their separation are based on immunofluorescent staining, which does not provide the information on the morphology.Materials and methods. The aim of this study was to evaluate how two different separation techniques affect cell morphology and to analyse cell morphology with techniques used in routine cytopathological laboratory. A direct side-by-side comparison of physical (Parsortix%) and biological (MACS%) separation technique was performed.Results. In the preclinical setting, both isolation techniques retained the viability and antigenic characteristics of MCF7 breast cancer cells. Some signs of degeneration such as cell swelling, cytoplasmic blebs, villous projections and vacuolization were observed. In metastatic breast cancer patient cohort, morphological features of isolated CTCs were dependent on the separation technique. After physical separation, CTCs with preserved cell morphology were detected. After biological separation the majority of the isolated CTCs were so degenerated that their identity was difficult to confirm.Conclusions. Taken together, physical separation is a suitable technique for detection of CTCs with preserved cell morphology for the use in a routine cytopathological laboratory.
Keywords: breast cancer; circulating tumor cells; CTC; morfologija; morphology; rak dojke